2016
DOI: 10.1002/ijc.30410
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to diet, physical activity and body weight recommendations and breast cancer incidence in the Black Women's Health Study

Abstract: Adherence to cancer prevention recommendations has been associated with lower incidence of breast cancer in previous studies, but evidence in African American women is limited. This project evaluated the association between adherence to the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) cancer prevention recommendations and breast cancer incidence among African American women. The Black Women’s Health Study (analytic cohort=49,103) is an ongoing prospective cohort study of Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 47 publications
(215 reference statements)
3
71
1
Order By: Relevance
“…Very few studies have examined these associations among Blacks. In studies conducted in the Black Women’s Health Study only 8.5% of women met at least 4 of the guidelines, and although no association was observed between increased adherence and colorectal cancer incidence [10], increasing adherence was also associated with reduced breast cancer incidence [7]. Another study reported that BMI mediated nearly 18% of the association between Black race and breast cancer mortality, though non-significant [34].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have examined these associations among Blacks. In studies conducted in the Black Women’s Health Study only 8.5% of women met at least 4 of the guidelines, and although no association was observed between increased adherence and colorectal cancer incidence [10], increasing adherence was also associated with reduced breast cancer incidence [7]. Another study reported that BMI mediated nearly 18% of the association between Black race and breast cancer mortality, though non-significant [34].…”
Section: Discussionmentioning
confidence: 99%
“…Cut points for physical activity were based on the American Health Association definitions for ideal, moderate, and poor physical activity . Cut points for sugar‐sweetened beverages, fruits and vegetables, fiber, red and processed meats, and alcohol were chosen to match those in other studies to maintain comparability . One hundred percent fruit juice and diet soft drinks were not considered to be sugar‐sweetened beverages.…”
Section: Methodsmentioning
confidence: 99%
“…After publication of the second expert report, numerous studies developed a composite score to measure adherence to the WCRF/AICR cancer prevention guidelines, which hereafter is called an adherence score. These studies reported a link between a higher adherence score and better quality of life, lower morbidity, and lower mortality from several types of cancer, including CRC …”
Section: Introductionmentioning
confidence: 98%
“…Based on studies evaluating the associations between lifestyle factors and cancer risk, the objective of these recommendations was to empower individuals to take actions to lead cancer‐free lives. Many studies conducted in Western populations have shown that adopting a favorable lifestyle pattern was associated with lower risks of overall and site‐specific cancers . For example, the European Prospective Investigation into Cancer and Nutrition (EPIC) study found that adherence to the 2007 WCRF/AICR guidelines was associated with reduced risks of overall or site‐specific cancers .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the European Prospective Investigation into Cancer and Nutrition (EPIC) study found that adherence to the 2007 WCRF/AICR guidelines was associated with reduced risks of overall or site‐specific cancers . There also was evidence indicating that the health benefits of the WCRF guidelines could be different in diverse populations . However, such studies in the Chinese population were limited.…”
Section: Introductionmentioning
confidence: 99%